2022
DOI: 10.3389/fpsyg.2022.979666
|View full text |Cite
|
Sign up to set email alerts
|

Work-life balance practices and organizational cynicism: The mediating role of person-job fit

Abstract: This study aims to elaborate on how work-life balance (WLB) practices influence organizational cynicism (OC) through the mediation effects of person-job fit (PJF). We collected data from 331 nurses through a self-administered survey, and we tested our hypothesized model through partial least square structural equation modeling techniques using SmartPLS software. The findings revealed that WLB practices influenced OC negatively and PJF positively. We further found that PJF negatively influenced OC and mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…The SET suggests that employees tend to reciprocate organisation support with positive attitudes (Blau, 1964). Those who telecommute or who are authorized to use telecommuting develop positive attitudes such as work-life balance and job satisfaction and are less likely to quit the job (De los Santos Jamal et al, 2021;Kakar et al, 2022a). Besides, the finding that telecommuting increases ER is also in agreement with the work of (Choi, 2019;Tsen et al, 2021), who found that flexible work arrangement such as telecommuting reduces employees' voluntary turnover.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The SET suggests that employees tend to reciprocate organisation support with positive attitudes (Blau, 1964). Those who telecommute or who are authorized to use telecommuting develop positive attitudes such as work-life balance and job satisfaction and are less likely to quit the job (De los Santos Jamal et al, 2021;Kakar et al, 2022a). Besides, the finding that telecommuting increases ER is also in agreement with the work of (Choi, 2019;Tsen et al, 2021), who found that flexible work arrangement such as telecommuting reduces employees' voluntary turnover.…”
Section: Discussionmentioning
confidence: 84%
“…Telecommuting has also been found to help employees vent their work-family conflict (Gajendran & Harrison, 2007). In addition, telecommuting provides employees autonomy in managing their family and work life (Felstead et al, 2002;Kakar et al, 2022a) and enables them to work from home, thus reducing daily commute expenses (O'Brien & Yazdani Aliabadi, 2020) and human-to-human contact (Chai et al, 2022). Research shows that people prefer to use telecommuting in order to avoid contact (Chai et al, 2022) and thus mitigate the threat or fear posed by COVID-19 (Iversen et al, 2022;Messner, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Chowdhury and Kang (2022), Kakar et al. (2022), and Rahman et al. (2022) have conceptualized person‐organization fit with values and goals congruence between person and organization, while Boon and Biron (2016), and Yu (2016) have used only values congruence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, job resources are those “physical, social, or organizational aspects of the job that are functional in achieving work goals, reducing job demands, or stimulating personal growth, learning, and development” (Llorens et al., 2006, p. 379). Within a working environment, an employee always seeks congruence with job resources and demands (Dawis & Lofquist, 1984; Kakar, Kruger, et al., 2022). The congruence of job demands with a person's KSAs is known as demand‐ability fit, while the congruence between job resources (e.g., pay, benefits, training, promotion, and growth opportunities) and individual psychological needs, desires, and preferences are termed as need‐supply fit (Kakar et al., 2022; Pattanawit & Charoensukmongkol, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Breach has been empirically validated as distinct from unmet expectations, and breach is a strong determinant of outcomes in the workplace (Robinson & Rousseau, 1994;Zhao, Wayne, Glibkowski, & Bravo, 2007). PCB was found to be empirically different from organizational cynicism Kakar et al, 2022), although both are generated by violations of social exchange (Johnson & O'Leary-Kelly, 2003). The organization's fulfillment of psychological contracts was conceptualized as a reflection of the employee's organizational support.…”
Section: Psychological Contract Breachmentioning
confidence: 99%